Optimisation d'un système photovoltaïque adapté par une commande MPPT basée sur les algorithmes intelligents - Toumi, Djaafar (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
Résumé : Solar PV systems are considered in this study and exhibited cost-effectiveness and better efficiency. For controlling the photovoltaic power, DC-DC buck converter has utilized in this thesis. Further, the Maximum Power Point Tracking (MPPT) mechanism is used in order to attain maximum efficiency. The main energy characteristics are analyzed and the mathematical models of the components of an autonomous PV system are developed to study the modes of tracking the MPP. The necessary conditions for matching the parameters of the PV and the DC-DC buck converter are evaluated to track the MPP. This thesis aims to create an original method and algorithm for calculating and selecting parameters of the main elements of a PV stations. The optimal value of the sampling time of the MPP controller is obtained for different schemes of the PV system. This research aims to increase the efficiency of the PV system by applying the improved particle swarm optimization (IPSO), perturb and observe (P&O), and incremental conductance algorithm in different cases of the operations. The simulation of dynamic modes of an autonomous photovoltaic (PV) station is performed in the MATLAB/SIMULINK software package. The simulation results of dynamic operations of the PV system show that the voltage converter and the MPP controller with the selected parameters according to the proposed method provide reliable and effective tracking of the MPP in all different connections of the PV systems الملخص: في هذه الدراسة تم النظر في أنظمة الطاقة الشمسية الكهروضوئية والتي أظهرت فعالية من حيث التكلفة وكفاءة أفضل. للتحكم في الطاقة الكهروضوئية، تم استخدام محول باك DC-DC . علاوة على ذلك يتم استخدام آلية تتبع نقطة الطاقة القصوى (MPPT)من أجل تحقيق أقصى قدر من الكفاءة ، ويتم تحليل خصائص ِالطاقة الرئيسية وتطوير النماذج الرياضية لمكونات النظام الكهروضوئي المستقل لدراسة طرق تتبع نقطة الاستطاعة العظمى (MPP) . يتم تقييم الشروط اللازمة لمطابقة معلمات PV و محول باك DC-DC لتحديد و تتبع نقطة الطاقة القصوى. (MPP) تهدف هذه الأطروحة إلى إنشاء طريقة وخوارزمية أصلية لحساب واختيار معلمات العناصر الرئيسية لمحطات الكهروضوئية. يتم الحصول على القيمة المثلى لوقت أخذ العينات لوحدة التحكم MPP لمخططات مختلفة من نظام PV. كما يهدف أيضًا إلى زيادة كفاءة النظام الكهروضوئي من خلال تطبيق تحسين سرب الجسيمات (IPSO) والاضطراب والمراقبة (P&O) وخوارزمية التوصيل الإضافي (InC) في حالات مختلفة من العمليات. يتم إجراء محاكاة للأنماط الديناميكية لمحطة كهروضوئية مستقلة (PV) في حزمة برامج MATLAB / SIMULINK. تظهر نتائج محاكاة العمليات الديناميكية للنظام الكهروضوئي أن محول الجهد ووحدة التحكم MPP مع المعلمات المحددة وفقًا للطريقة المقترحة توفر تتبعًا موثوقًا وفعالًا لـ MPPفي جميع التوصيلات المختلفة للأنظمة الكهروضوئية
أطروحة دكتوراه تخصص شبكات كهربائية في العلوم التكنولوجيا
Keywords: sampling time, Maximum power controller, Photovoltaic stations, DC–DC buck converter; محطات كهروضوئية ، DC – DC محول باك، ماتلاب / سيمولينك ، وقت الحصول على العينات، التحكم المنطقي الضبابي (FLC) ، تتبع الحد الأقصى لنقطة الطاقة (MPPT) ، القلق والمراقبة(P&O) ، المصفوفة الكهروضوئية (PV)